2022
DOI: 10.3389/fpsyg.2022.905890
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Knowledge Hiding Behaviors Through Workplace Friendship and Altruistic Leadership, and Mediating Role of Positive Emotions

Abstract: Studies related to knowledge hiding prevention are limited and need attention. Hence, the present study attempts to measure the direct impact of workplace friendship and altruistic leadership on preventing the knowledge hiding behavior; and also, in the presence of positive emotions. The study has also checked the mediating role of positive emotions in these relationships. The target population of the study is the employees working in the government sector (sample size of 496). The present study has employed q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…We also tested the impacts of EPE in Study 3. According to existing studies, employees’ behaviors are closely related to emotions ( He and Wei, 2022 ). Findings about high-activated positive mood (e.g., enthusiastic, inspired, and excited) have also indicated that positive emotions can lead to positive behavior ( Mindeguia et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We also tested the impacts of EPE in Study 3. According to existing studies, employees’ behaviors are closely related to emotions ( He and Wei, 2022 ). Findings about high-activated positive mood (e.g., enthusiastic, inspired, and excited) have also indicated that positive emotions can lead to positive behavior ( Mindeguia et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…An altruistic leader's admiration may encourage followers to expand and strengthen their social networks, which raises the possibility that they will assist individuals needing their expertise. Humility, patience, comprehension, compassion, and kindness are the sources of this love (He & Wei, 2022). The current study also assumes that an altruistic leader's selfless and helpful actions will improve knowledge-sharing behavior.…”
Section: Altruistic Leadership and Khmentioning
confidence: 96%
“…At present, a kind of headache for managers is widespread in organizations, that is, knowledge hiding (Peng, 2013;Singh, 2019). Studies have shown that employees in smart healthcare firms, telecom sector, the government sector and academic institutions all reported that they had the experience of deliberately hiding knowledge (Cao, 2022;He and Wei, 2022;Qi and Ramayah, 2022;Wang and Dong, 2022).…”
Section: Introductionmentioning
confidence: 99%